2018
DOI: 10.1002/joc.5889
|View full text |Cite
|
Sign up to set email alerts
|

On bias correction of summer monsoon precipitation over India from CORDEX‐SA simulations

Abstract: In the present study, four different bias correction methods are assessed in improving the precipitation output from a set of two regional climate simulations for 1971–2005 period. The simulations come from Coordinated Regional Climate Downscaling Experiment over South Asia (CORDEX‐SA). The bias correction methods applied here are linear scaling (Scaling), empirical quantile mapping (EQM), power transformation (PTR) and local intensity scaling (LOCI). All the bias correction techniques show skill in improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 91 publications
3
8
0
Order By: Relevance
“…The findings from the study are supported by the results from Choudhary and Dimri (2019), which show improved performance of rainfall simulations in India after bias correction. They concluded that the EQM method performed best relative to LOCI and SCL.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The findings from the study are supported by the results from Choudhary and Dimri (2019), which show improved performance of rainfall simulations in India after bias correction. They concluded that the EQM method performed best relative to LOCI and SCL.…”
Section: Resultssupporting
confidence: 79%
“…The findings are again complemented by the results in Choudhary and Dimri (2019). For inter‐annual variability (as standard deviation) of JJAS mean precipitation, the application of EQM on RCA4 data could successfully capture the spatial pattern of variability.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations